(untitled) (CIPEEX, 2025)
Erythrocytes are blood cells that transport oxygen to all tissues. They have a biconcave shape and are thicker on the sides and smaller in the center. Morphological changes in red blood cells are alterations in size, color and shape, and can be directly related to pathological abnormalities. Poikilocytosis is a change in the shape of red blood cells circulating in the blood, which can become rounded, sphere-shaped, teardrop-shaped, sickle-shaped or spiculated, which can interfere with their function. This study aims to describe the importance of morphological changes in erythrocytes in diagnosis. It is a narrative bibliographic review, with searches in the Scielo and Pubmed databases included in the years 2019 and 2024, excluding those that did not meet the theme. Hematological alterations can be seen in anemias and other pathologies, so it is important to identify them in order to differentiate the diagnosis. Drepanocytes, synonymous with sickle-shaped red blood cells, erythrocytes acquire this shape due to the presence of Hemoglobin S, which polymerizes and precipitates in the cell membrane, causing deformation, and is found in sickle cell diseases. Elliptocytes are red cells with an oval or elongated shape, common in hereditary elliptocytosis, caused by mutations in cytoskeletal genes, such as spectrin. These alterations affect the flexibility of red blood cells and can lead to hemolysis. Spherocytes are RBCs with a spherical shape and reduced biconcavity, losing the central clear halo and showing microcytosis, this is due to the loss of part of the membrane, maintaining the hemoglobin content, they are denser and more stained than normal erythrocytes. Acanthocytes consist of erythrocytes with few projections and irregular around the membrane. They are mainly present in severe liver diseases, as well as in hemolytic anemias in general. Dacryocytes, or “teardrop-shaped cells”, are deformed red blood cells. These cells have a shape similar to a teardrop and indicate alterations in the production of red blood cells, usually associated with diseases affecting the bone marrow. Stomatocytes are cells with a lighter central area that resembles a mouth. They are associated with hereditary disorders, such as stomatocytosis, and can indicate problems in the osmotic balance of the cells, resulting in cell swelling. Codocytes, also known as target cells, are red blood cells with an irregular distribution of hemoglobin, which gives them this characteristic shape. They are generally related to hemoglobinopathies (SS, SC), thalassemias, hepatopathies, splenectomized patients and iron deficiency anemia. These morphological variations in erythrocytes provide important diagnostic information that helps direct the treatment of underlying conditions, highlighting the importance of morphological analysis in hematological diagnosis..Bibliography: Bandaru SS, Killeen RB, Gupta V. Poikilocytosis. 2023 Apr 3. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2024 Jan–. PMID: 32965812.Dzierzak E, Philipsen S. Erythropoiesis: development and differentiation. Cold Spring Harb Perspect Med. 2013 Apr 1;3(4):a011601. doi: 10.1101/cshperspect.a011601. PMID: 23545573; PMCID: PMC3684002.HOFFBRAND, A. V.; MOSS, P. A. H. Fundamentos em hematologia de Hoffbrand. 7. ed. Porto Alegre: Artmed, 2018.